Migration flows in commodity cycles: Assessing the role of migration policies - Duncan, Alan; Harris, Mark N; Mavisakalyan, Astghik; Nguyen, Toan (Elsevier, 2020)
This paper sheds light on the role of immigration policies in shaping immigration flows in responses to labor market changes. Using data from Australia during the 2001 to 2015 commodity cycle as a quasi-experiment, we find that employer-sponsored (demand-driven) immigration varied in line with commodity prices, with commodity-intensive states witnessing stronger growth rates than remaining states over the resources boom period. There is no evidence of any such patterns for points-based (supply-driven) immigrants. Moreover, we do not find either employer-sponsored or point-based migration flows increase in the non-tradable sector relative to the tradable sector in a triple-differences analysis with state-industry level data. These findings emphasize the importance of employer-sponsored immigration in alleviating short-term local labor shortages.